Regional-scale interactions between groundwater and surface water under changing aridity: evidence from the River Awash Basin, Ethiopia. Issue 3 (17th February 2021) - Kebede, Seifu; Charles, Katrina; Godfrey, Samuel; MacDonald, Alan; Taylor, Richard G.
ABSTRACT: Relationships between surface waters and groundwaters at basin scale are rarely investigated but have important implications for water resource development and management. Here, we integrate evidence from geochemical tracers and piezometry to advance the understanding of regional-scale, groundwater–surface water interactions in the River Awash Basin of Ethiopia. Hydrological characteristics are consistent with those observed in other semi-arid and arid basins where rivers are predominantly losing and act as a source of recharge rather than as a sink for groundwater discharge. Further, regional groundwater flow originating from the highlands exits the catchment rather than discharging to the riverine drainage. Consequently, groundwater abstraction from several regional-scale aquifers in the lowlands is not expected to impact river flow. However, salinity presents a major threat to irrigation and water supply. We identify critical areas for managing inflows, water use, wetlands and water quality that have significant implications for water security across the basin.